The P300 auditory event-related potential as a method to assess the benefit of contralateral hearing aid use in bimodal listeners: a proof-of-concept. (2nd January 2020) - Van Yper, Lindsey N.; Dhooge, Ingeborg J. M.; Vermeire, Katrien; De Vel, Eddy F. J.; Beynon, Andy J.
Abstract: Objective: Bimodal listeners vary in the amount of benefit they receive from wearing the contralateral hearing aid. This may partially depend on the listener's auditory processing capacities. The current study explores whether the P300 event-related potential can provide insight into the mechanisms underlying the benefits of wearing a contralateral hearing aid. Design: P300s were recorded using an oddball paradigm with 500 and 250 Hz tone-bursts as standard and deviant stimuli, respectively. Subjects counted the number of deviants – a measure of performance. N2b latencies, P300 latencies, N2b-P300 amplitudes, and performance were assessed during CI-only and bimodal listening. Study sample: Five bimodal listeners. Results: P300s were present in four subjects. Amplitudes were larger during bimodal listening (bimodal: 22.3 ± 4.83 µV, CI-only: 13.1 ± 3.86 µV). Both N2b and P300 latencies were shorter during bimodal (N2b: 265 ± 20.0 ms, P300: 551 ± 129.4 ms) than CI-only listening (N2b: 326 ± 42.2 ms, P300: 402 ± 38.4 ms). While performance often reached ceiling level, the difference between the standard and deviant was generally more salient during bimodal listening. Conclusions: This study provides a proof-of-concept, suggesting that P300s may provide insight into benefits that are not always measurable with behavioural tasks.